1999
DOI: 10.1159/000026416
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to the Synthetic Cannabinoid HU-210: Effects on the Endocrine and Immune Systems of the Adult Male Offspring

Abstract: Natural and synthetic cannabinoid receptor agonists have been described to exert profound effects on both the neuroendocrine integration and the functional responses of the immune system. In the present study, Wistar rats were exposed to the highly potent cannabinoid agonist HU-210 (1, 5 and 25 μg/kg) during gestation and lactation and the ensuing effects on several endocrine and immune parameters of the adult male offspring were analyzed. Perinatal exposure to HU-210 partially affected the distribution of lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 39 publications
(74 reference statements)
0
14
0
Order By: Relevance
“…Daily oral 1, 5 and 25μg/kg HU-210 exposure to pregnant rats had no significant effect on gestational progression or post-natal food and water intake when compared to controls (del Arco et al, 2000). Offspring exposed to HU-210 in utero showed no significant difference from the non-exposed control group in average birth weight, body length, and lymphocyte immune function; however, 1μg/kg HU-210-exposed rats had a 17% increase in spleen size.…”
Section: Resultsmentioning
confidence: 86%
“…Daily oral 1, 5 and 25μg/kg HU-210 exposure to pregnant rats had no significant effect on gestational progression or post-natal food and water intake when compared to controls (del Arco et al, 2000). Offspring exposed to HU-210 in utero showed no significant difference from the non-exposed control group in average birth weight, body length, and lymphocyte immune function; however, 1μg/kg HU-210-exposed rats had a 17% increase in spleen size.…”
Section: Resultsmentioning
confidence: 86%
“…Perinatal exposure to (6aR,10aR)-9-(hydroxymethyl)-6,6-dimethyl-3-(2-methyloctan-2-yl)-6a,7,10,10a-tetrahydrobenzo[c]chromen-1-ol (HU-210), a cannabinoid agonist, caused altered distribution of lymphocyte subpopulations in the spleen and peripheral blood of Wistar rats. In addition, there was a reduction in the T helper subpopulation in the spleen and a decrease in the rate of T helper/T cytotoxic cells in peripheral blood (del Arco et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that adult female rats exposed to THC during pregnancy and lactation exhibited higher levels of both corticotrophin releasing factor (CRF-41) in the medial basal hypothalamus and plasma corticosterone, whereas THC-exposed males showed lower levels of both endocrine parameters (Navarro et al 1995; Rubio et al 1995). In a subsequent study, the same group showed that perinatal exposure to doses of the synthetic cannabinoid agonist HU-210 equipotent to human cannabis consumption resulted in a dose-dependent decrease in plasma corticosterone levels in the adult male offspring, and in clear alterations in the responsiveness of the HPA axis to an acute stimulatory challenge with HU-210 (del Arco et al 2000). The authors suggest that these endocrine alterations might reflect compensatory mechanisms for the presence of higher levels of corticosterone during fetal development following a HU-210-induced increase in corticosterone in maternal blood (Rodriguez de Fonseca et al 1995; Ward and Weisz 1984).…”
Section: Long-term Neuroendocrine Effects Induced By Maternal Cannabimentioning
confidence: 99%
“…The authors suggest that these endocrine alterations might reflect compensatory mechanisms for the presence of higher levels of corticosterone during fetal development following a HU-210-induced increase in corticosterone in maternal blood (Rodriguez de Fonseca et al 1995; Ward and Weisz 1984). Interestingly, offspring perinatally exposed to high levels of the synthetic cannabinoid agonist showed a decreased responsiveness of the HPA axis to stressors at adult ages, whereas offspring perinatally exposed to low levels of the same cannabinoid compound showed a sensitization of the HPA axis (del Arco et al 2000). These data point out that maternal exposure to even low doses of cannabinoid compounds induces long-lasting alterations in the functionality of the HPA axis that, in turn, might result in an impairment in the behavioral and neuroendocrine response to stress in the adult offspring.…”
Section: Long-term Neuroendocrine Effects Induced By Maternal Cannabimentioning
confidence: 99%